Ethnographic Gameness: Theorizing Extra-methodological Fieldwork Practices in a Study of Outlaw Motorcycle Clubs. (February 2021) - Schmid, Christian Johann
This article theorizes the fieldwork experiences that I gained while studying outlaw biker subculture. Drawing on Bourdieu's practice theory and Goffman's dramaturgical interactionism, I argue that ethnography in practice is pre-disposed by the ethnographer's primary habitus, which shapes symbolic interaction. To substantiate this claim, I disclose my own upbringing in a troubled working-class family and my personal ties with outlaw bikers, both prior to and beyond my research. This article then illustrates how my habitus helped me to compensate for the vagueness of ethnography in theory with regard to three recurrent issues of fieldwork, which are the practices of (1) approaching/entering the field, (2) negotiating participation, and (3) managing (un)fortunate circumstances. After reflecting on my cleft habitus as the buddy and/or researcher in ethnographic practice, this article concludes with the metaphor of gameness. This concept, which is borrowed from early prize fighting, is used to outline and label the ideal-type of the ethnographer who is well-suited for the immersion into deviant, criminalized, or otherwise culturally elitist fields.